An energy based peridynamic state‐based failure criterion. Issue 1 (17th December 2018) - Willberg, Christian; Rädel, Martin
Abstract: The paper presents a verification and convergence study of an enhanced energy based failure model based on Foster et al. [2]. The failure model has been implemented in the open source software Peridigm. The study is performed with a virtual double cantilever beam test. To verify the implementation an energy release rate is virtually measured and compared with the input data. Time and load of the crack initiation are used as the convergence criteria.